Effect of dual inoculation of arbuscular mycorrhizal fungus and Rhizobium on chlorophyll content of pigeon pea [Cajanus cajan (L.) Mill sp.] (Journal of Bio-Science, 2018)
Abstract not availableJ. bio-sci. 24: 83-85, 2016